I MPLEMENTASI KEBIJAKAN PENERAPAN SISTEM KREDIT SEMESTER DI SMA NEGERI 1 LAWANG - Jumad Jumad (Jurnal Penelitian Kebijakan Pendidikan, 2021)
The purpose of this research is to describe the implementation of semester credit sistem at SMA Negeri 1 Lawang. This means the research aims to find out how the semester credit sistem is applied at SMA Negeri 1 Lawang, the obstacles, and the efforts made to overcome them. This is policy research that uses a qualitative approach. Data collection methods used in this study were interviews, observations, document and archive studies. The informants in this study were the principal, vice principal in curriculum, teachers, school committees, and students. The data were analyzed using descriptive analysis following the stages of data reduction, data presentation, making conclusions and verification. The results of this study indicate that the application of the semester credit sistem at SMA Negeri 1 Lawang is a new semester credit sistem and its application is in accordance with the Regulation of Ministry of Education and Culture (Permendikbud) Number 158 of 2014. The obstacles faced in implementing the semester credit sistem were the lack of teacher commitment and support from parents whose children belong to the fast-learning group. Efforts made to overcome the problems were to choose teachers who had strong commitment and to conduct dissemination to parents and employing a statement letter.